(untitled) (Journal of Partial Differential Equations, 2000)
This paper is concerned with the semilinear heat equation u_t = Δu - u^-q in Ω × (0, T) under the nonlinear boundary condition ∂u∂v = u^p on ∂Ω × (0, T). Criteria for finite time quenching and blow-up are established, quenching and blow-up sets are discussed, and the rates of quenching and blow-up are obtained.